UPAYA MENINGKATKAN PRESTASI SISWA DALAM MEMBUAT ARANSEMEN MUSIK POPULER MELALUI MEDIA PIANIKA PADA KELAS IX DI SMPN 2 KATAPANG KAB. BANDUNG - Ucu Sumiati (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2022)
This research is knowing the success rate of students in creativity in making popular music arrangements through pianika media in class IX of SMP Negeri 2 Katapang Bandung Regency so that learning becomes more effective and quality, as well as describing active, innovative, creative, effective and fun learning. The research method used is the class action research method. This method is carried out through surveys, descriptive analysis and experimentation. The subjects of the study were 36 people consisting of 19 female students and 17 men. This subject was chosen based on the results of the initial test, namely semester 1, which showed that class IX had a grade average score and low completion and the enthusiasm for learning music on this material was low compared to other classes. The data collection techniques used are tests, observations, questionnaires, interviews and documentation. The data analysis technique used is an interactive model that has four components, namely data collection, data reduction, data presentation, and drawing conclusions or verification. In this study, the criteria for successful action for learning achievement were with a complete limit of 75 (KKM = 75) and a class completion of 85%. The results showed that there was an increase in student achievement in (creativity in making arrangements of popular music) through classical pianica media before pre-action was 12/36 X 100 % = 33.33%, (still relatively low) and the percentage of student success in (creativity in making arrangements of popular music) through the medium of pianica after action (cycle 1) was 24 / 36 X 100 = 66.66% (still relatively high).